Survey of the perceptions of key stakeholders on the attributes of the South African Notifiable Diseases Surveillance System - F. G. Benson; A. Musekiwa; L. Blumberg; L. C. Rispel (BMC, 2016)
Abstract Background An effective and efficient notifiable diseases surveillance system (NDSS) is essential for a rapid response to disease outbreaks, and the identification of priority diseases that may cause national, regional or public health emergencies of international concern (PHEICs). Regular assessments of country-based surveillance system are needed to enable countries to respond to outbreaks before they become PHEICs. As part of a broader evaluation of the NDSS in South Africa, the aim of the study was to determine the perceptions of key stakeholders on the national NDSS attributes of acceptability, flexibility, simplicity, timeliness and usefulness. Methods During 2015, we conducted a nationally representative cross-sectional survey of communicable diseases coordinators and surveillance officers, as well as members of NDSS committees. Individuals with less than 1 year experience of the NDSS were excluded. Consenting participants completed a self-administered questionnaire. The questionnaire elicited information on demographic information and perceptions of the NDSS attributes. Data were analysed using descriptive statistics and the unconditional logistic regression model. Results Most stakeholders interviewed (53 %, 60/114) were involved in disease control and response. The median number of years of experience with the NDSS was 11 years (inter-quartile range (IQR): 5 to 20 years). Regarding the NDSS attributes, 25 % of the stakeholders perceived the system to be acceptable, 51 % to be flexible, 45 % to be timely, 61 % to be useful, and 74 % to be simple. Health management stakeholders perceived the system to be more useful and timely compared to the other stakeholders. Those with more years of experience were less likely to perceive the NDSS system as acceptable (OR 0.91, 95 % CI: 0.84-1.00, p = 0.041); those in disease detection were less likely to perceive it as timely (OR 0.10, 95 % CI: 0.01-0.96, p = 0.046) and those participating in National Outbreak Response Team were less likely to perceive it as useful (OR 0.38, 95 % CI: 0.16-0.93, p = 0.034). Conclusion The overall poor perceptions of key stakeholder on the system attributes are a cause for concern. The study findings should inform the revitalisation and reform of the NDSS in South Africa, done in consultation and partnership with the key stakeholders.